WOMEN-WRITERS IN ENGLISH LITERATURE. - Mo’ydinova Umida; Eldorbek Erkinovich Hamitov (Ta’lim innovatsiyasi va integratsiyasi, 2024)
This article provides an overview of the contribution of women writers to English literature throughout history. Beginning with early pioneers such as Jane Austen and the Brontë sisters, the discussion traces the evolution of women's voices in literature, exploring the societal challenges they faced and the themes they addressed. The article examines key works by women writers across different genres, highlighting their impact on literary movements and their role in shaping cultural narratives. Furthermore, it analyzes the changing attitudes towards women's writing and the emergence of feminist literary criticism. By exploring the diverse perspectives and narratives of women writers, this article aims to underscore their significance in enriching the literary landscape and challenging conventional literary norms.